2014
DOI: 10.1038/npp.2014.51
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D3 Receptor Is Necessary for Ethanol Consumption: An Approach with Buspirone

Abstract: Mesolimbic dopamine (DA) controls drug- and alcohol-seeking behavior, but the role of specific DA receptor subtypes is unclear. We tested the hypothesis that D3R gene deletion or the D3R pharmacological blockade inhibits ethanol preference in mice. D3R-deficient mice (D3R−/−) and their wild-type (WT) littermates, treated or not with the D3R antagonists SB277011A and U99194A, were tested in a long-term free choice ethanol-drinking (two-bottle choice) and in a binge-like ethanol-drinking paradigm (drinking in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 69 publications
5
45
1
1
Order By: Relevance
“…In another study, increases in BDNF and D3 receptor expression were found in the NAcc of rats that received sensitizing doses of morphine in a distinct environment (Liang et al, 2011). Increased of D3 receptor have been reported also following alcohol exposure (Leggio et al, 2014; Vengeliene et al, 2006) and nicotine exposure (Le Foll et al, 2003a; Le Foll et al, 2003b). …”
Section: D3 Receptor Densitiesmentioning
confidence: 98%
“…In another study, increases in BDNF and D3 receptor expression were found in the NAcc of rats that received sensitizing doses of morphine in a distinct environment (Liang et al, 2011). Increased of D3 receptor have been reported also following alcohol exposure (Leggio et al, 2014; Vengeliene et al, 2006) and nicotine exposure (Le Foll et al, 2003a; Le Foll et al, 2003b). …”
Section: D3 Receptor Densitiesmentioning
confidence: 98%
“…Overexpression of D 2 transiently increased intake in D 2 receptor knockout mice and decreased intake in wild-type mice (Thanos, Rivera, et al, 2005). Effects of D 3 and D 4 dopamine receptor deletion are less well studied, but there is a report of substantially decreased alcohol consumption in 2BC and DID tests in D 3 knockout mice (Leggio et al, 2014). An example of the complex role of sex and genetic background is illustrated by the DAT knockout, which decreased drinking in females but not males on a B6 background and increased drinking in males but not females on a mixed genetic background (Table 3).…”
Section: Neurotransmitter Systemsmentioning
confidence: 99%
“…In this regard, the drug buspirone (Buspar s , a marketed anxiolytic mainly used for its serotonergic effects) was recently shown to have D 3 antagonist properties in vitro (Bergman et al, 2013;Kula et al, 1994). Studies in nonhuman primates showed buspirone to decrease cocaine selfadministration at acute doses that are clinically relevant in humans (Bergman et al, 2013;Czoty and Nader, 2015), and chronic dosing regimens also showed efficacy in reducing cocaine, ethanol and nicotine self-administration in primates and mice (Leggio et al, 2014;Mello et al, 2013aMello et al, , 2013bSkolnick, 2010). In humans, several studies have evaluated the efficacy of buspirone in clinical trials of addictions (with mixed results; reviewed in Paterson et al, 2014), and a recent pilot study of methamphetamine dependence suggested that buspirone may dampen subjective responses to methamphetamine (Paterson et al, 2014).…”
Section: Usefulness Of [ 11 C]-(+)-phno In Testing the D 3 Antagonismmentioning
confidence: 99%